Answer:
the equation is
y = 0.75x
And, the constant of proportionality is 0.75
Step-by-step explanation:
The computation is shown below:
Given that
4y = 3x
And,
12y = 9x
Here the equation that represent proportional relationship is
4y = 3x
Divide both sides by 4
y = 3x ÷ 4
Now
12y = 9x
divides both sides by 12
y = 9 ÷ 12x
y = 3 ÷ 4x
y = 0.75x
so the equation is
y = 0.75x
And, the constant of proportionality is 0.75
Proving a relation for all natural numbers involves proving it for n = 1 and showing that it holds for n + 1 if it is assumed that it is true for any n.
The relation 2+4+6+...+2n = n^2+n has to be proved.
If n = 1, the right hand side is equal to 2*1 = 2 and the left hand side is equal to 1^1 + 1 = 1 + 1 = 2
Assume that the relation holds for any value of n.
2 + 4 + 6 + ... + 2n + 2(n+1) = n^2 + n + 2(n + 1)
= n^2 + n + 2n + 2
= n^2 + 2n + 1 + n + 1
= (n + 1)^2 + (n + 1)
This shows that the given relation is true for n = 1 and if it is assumed to be true for n it is also true for n + 1.
<span>By mathematical induction the relation is true for any value of n.</span>

=

, and when you multiply it by 5 it turns into

, which is

So in conclusion he watched 9 & 10 minutes watching the movie
Let x the subject of the equation in x-2y=-10 this make it x=2y-10 substitute this in the first equation. 3(2y-10)-2y=-6 solve for y, y=6. substitute y in any of the original equations to get x x= 2